Culture in the psychoanalytical concept of Karen Horney - Ratushnyi, Denys (Ukrainian Cultural Studies, 2022)
The purpose of the publication is to analyze views of American psychoanalytic Karen Horney on the relationship between culture and mental life. The main methodological principles of K. Horney are defined: rejection of causal relationship between childhood and mental processes in adult age; rejection of primacy of biological and physiological factors in mental life; rejection of attempts to create universal psychology of humankind. These changes in methodology are the main distinction between Horney's concepts and orthodox Freudianism that also had caused conflict between them. It is found that the main research guideline of K. Horney is the recognition of the influence of culture on the mental life of a person. Culture is understood by K. Horney as a set of values in society that form the demands for an individual. Contradictory demands become the main source of neurosis – repression out anxiety and suppression drives. K. Horney defines the central problem of modern society as competition, which implies aggressive achievement of success. Competition, according to K. Horney, contradicts the desire to gain affection, which is why the "neurotic personality of our time" is formed. Also analyzed are the discussions around whether Karen Horney's theory can be considered psychoanalytic. Despite the criticism of orthodox Freudians, Horney emphasized that her departure from classical psychoanalysis is possible only on the basis of Freud's discoveries. At the same time, whether her concept belongs to psychoanalysis depends on what to consider essential in it: following the dogmas formulated by Freud, or the study of unconscious processes of the human psyche. Since Horney herself adheres to the second thesis, from her point of view she remains a psychoanalyst, as evidenced by her founding of the Association for the Advancement of Psychoanalysis
Keywords: culture; neurosis; competition; psychoanalysis; anxiety